Cholesterol-induced Thrombogenicity of the Vessel Wall: Inhibitory Effect of Fluvastatin - Camera, Marina; Toschi, Vincenzo; Comparato, Carmen; Baetta, Roberta; Rossi, Francesca; Fuortes, Michele; Ezekowitz, Michael D.; Paoletti, Rodolfo; Tremoli, Elena (Thrombosis and Haemostasis, 2002)
High cholesterol levels are a known risk factor for coronary events. The molecular links between high serum cholesterol and the increased thrombogenicity of the arterial wall are still matter of investigation. In the present study we investigate the relationship between plasma cholesterol, thrombus formation and TF expression in a atherosclerotic rabbit model.Hypercholesterolemic rabbits showed a pronounced TF staining as well as NF-κB activation in the aortic arch. A consistent vessel wall platelet deposition was also observed. Treatment with fluvastatin reduced lipid accumulation, TF overexpression (-60%), NF-κB activation, and platelet deposition (-56%). In vitro studies showed that the drug upregulated IκBa in unstimulated as well as in TNFa-stimulated cells and also impaired the TNF-α-induced Cdc42 prenylation, indicating that fluvastatin interferes with the transcriptional activation of TF gene.These results indicate that the prothrombotic phenotype of arterial wall, associated with elevated serum cholesterol levels, is mediated by TF overexpression. Fluvastatin treatment reduces the prothrombotic tendency by inhibiting TF synthesis.
Keywords: Thrombosis; atherosclerosis; hypercholesterolemia; tissue factor